Higher‐than‐expected population prevalence of potentially pathogenic germline TP53 variants in individuals unselected for cancer history. Issue 12 (21st September 2017) - de Andrade, Kelvin César; Mirabello, Lisa; Stewart, Douglas R.; Karlins, Eric; Koster, Roelof; Wang, Mingyi; Gapstur, Susan M.; Gaudet, Mia M.; Freedman, Neal D.; Landi, Maria Teresa; Lemonnier, Nathanaël; Hainaut, Pierre; et al.
Abstract: Li–Fraumeni syndrome (LFS) is an autosomal‐dominant cancer predisposition disorder associated with pathogenic germline variants in TP53, with a high penetrance over an individual's lifetime. The actual population prevalence of pathogenic germline TP53 mutations is still unclear, most likely due to biased selection of cancer affected families. The aim of this study was to estimate the population prevalence of potentially pathogenic TP53 exonic variants in three sequencing databases, totaling 63, 983 unrelated individuals. Potential pathogenicity was defined using an original algorithm combining bioinformatic prediction tools, suggested clinical significance, and functional data. We identified 34 different potentially pathogenic TP53 variants in 131 out of 63, 983 individuals (0.2%). Twenty‐eight (82%) of these variants fell within the DNA‐binding domain of TP53, with an enrichment for specific variants that were not previously identified as LFS mutation hotspots, such as the p.R290H and p.N235S variants. Our findings reveal that the population prevalence of potentially pathogenic TP53 variants may be up to 10 times higher than previously estimated from family‐based studies. These results point to the need for further studies aimed at evaluating cancer penetrance modifiers as well as the risk associated between cancer and rare TP53 variants. Abstract : We combined bioinformatic analyses with published functional and clinical data to evaluate the population prevalence of potentially pathogenic germline TP53 variants in three sequencing databases composed of 63, 983 unrelated individuals from different ethnic ancestries. Pathogenic or likely pathogenic germline TP53 variants were present in 0.06% to 0.2% of individuals. These values are considerably higher than previous projections from family‐based studies. This observation suggests that the actual penetrance of cancer in pathogenic TP53 variant carriers may be lower than previously described.